Cardiac troponin T is associated with mortality in patients admitted to critical care in a UK major trauma centre: a retrospective database analysis. (May 2019) - Crewdson, Kate; Thompson, Julian; Thomas, Matt
Background: Elevated levels of cardiac troponin T are associated with poor outcome in critically ill patients and have been proposed as a prognostic marker in major trauma. This study investigated the relationship between cardiac troponin T levels on admission to intensive care unit (ICU) and all-cause mortality in major trauma patients. Methods: A retrospective database analysis of cardiac troponin T levels on admission to the ICU in major trauma patients between 1 August 2015 and 31 December 2016 at a UK Major Trauma Centre was performed. Results: Of the 243 patients, 69 (28.4%) died. Cardiac troponin T levels were significantly higher in patients who died compared to survivors: 42 vs. 13 ng/L, respectively ( p < 0.0001); the odds of all-cause mortality increased significantly as troponin increased, independent of age or Acute Physiology and Chronic Health Evaluation score. Discussion: This confirms cardiac troponin T at ICU admission as a marker of mortality in major trauma. Elevated cardiac troponin T may be seen in patients without evidence of direct cardiac trauma.